“To Repair the World” with Paul Farmer, the lawyer for the least of the Earth: Paul Farmer, from English to Italian: opening up and restyling pragmatic thinking - Bela, Jean-Gabriel (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
In the aftermath of the Covid 19 health crisis that has hit and battered Italy, subversive thinking such as that of the US physician and anthropologist Paul Farmer and his holistic approach to illness and the sick could be a revolutionary opportunity in the care and accompaniment of the infirm. Died in 2022, Paul Farmer fought the unbridled capitalism that has engulfed all fields of human life and endangered even the sphere of public health. Horrified by financial speculation on people’s health and its social consequences of excluding the poorest from welfare, of which health is an essential component, Farmer proposes to re-imagine just public health policies at the core of which is equity and sensitivity to the suffering of others. And this is one of the reasons why reviewing one of his scholarly works is of paramount importance. Farmer’s text being reviewed has a high ethical value and combines the caring professions with the urgency of realigning inequalities.